RELEVANCE OF PRE-CONTRACTUAL ARRANGMENTS FOR JURISDICTION AND MERITS IN INTERNATIONAL INVESTMENT ARBITRATION - Đajić, Sanja (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
In this article the author discusses the issue whether pre-contractual arrangements and pre-investment expenditures may qualify for an investment within the meaning of applicable legal framework. The answer to this question is relevant for jurisdiction of investment tribunals. Chronological overview of cases dealing with pre-contractual arrangements demonstrates the shift from the original position according to which pre-investment expenditures do not amount to an investment to the understanding that pre-contractual arrangement may amount to an investment under certain circumstances, such as extensive definitions of an investment coupled with the existing investment in the host country. While there has been a significant shift recently which favored jurisdiction of investment tribunals, the established position of majority of tribunals in denying claims for loss of profits on the basis of failed commercial transactions remained unchanged.